MODAL MANUSIA PADA INDUSTRI TENUN SONGKET SAMBAS DI KABUPATEN SAMBAS KALIMANTAN BARAT (POTRET DAN KARAKTERISTIKNYA) - JAMALIAH, JAMALIAH (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
One attempt to boost economic growth is doing construction industry sector. Industrial development is intended to strengthen the national economic structure, improve the durability of the economy, expand employment and business opportunities, and at the same time promoting the growth of other development sectors.Interest is expected to be achieved through the efforts of improvement include improving the quality of human resources, provide adequate facilities and infrastructure, regulated bureaucracy and other policies that encourage the achievement of the industrial sector.The purpose of this study are as follows: 1 .To provide an overview of the situation and the social, economic and demografipekerja on household industry weaving in Sambas district. 2. To provide an overview of the historical development of domestic industries of weaving and characteristics of the variables in the form, output and wages of workers, labor resources, working capital, and product pricing, marketing, payment or the income level of workers, the range of products and others.